2010 14th International Conference Information Visualisation 2010
DOI: 10.1109/iv.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immersive Virtual Reality on Visualisation for a Design Review in Construction

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Research works indicate that exploring a design proposal from a user perspective may be beneficial to evaluate its compliance against performance-based requirements, taking into account the needs of the prospective occupants that will use the building spaces based on their related functional destinations (Hilfert and König, 2016;Simeone et al, 2013;Shen and Shen, 2011). Several research works describe the use of VR in pre-occupancy evaluations in order to predict human-building interactions that can feed designers and researchers with reliable user behaviour and occupant-related data (Bassanino et al, 2010;Kuliga et al, 2015;Adi and Roberts, 2014;Heydarian et al, 2015a;Heydarian et al, 2015b, Heydarian et al, 2015cHeydarian et al, 2017). For example, Heydarian et al (2015a) used immersive virtual environments to collect data on behaviours and preferences of occupants in relation to lighting conditions and so evaluating design options aiming to both meet their lighting preferences and, at the same time, increase the energy efficiency of the building.…”
Section: Immersive Virtual Reality In Usability-focused Design Reviewsmentioning
confidence: 99%
“…Research works indicate that exploring a design proposal from a user perspective may be beneficial to evaluate its compliance against performance-based requirements, taking into account the needs of the prospective occupants that will use the building spaces based on their related functional destinations (Hilfert and König, 2016;Simeone et al, 2013;Shen and Shen, 2011). Several research works describe the use of VR in pre-occupancy evaluations in order to predict human-building interactions that can feed designers and researchers with reliable user behaviour and occupant-related data (Bassanino et al, 2010;Kuliga et al, 2015;Adi and Roberts, 2014;Heydarian et al, 2015a;Heydarian et al, 2015b, Heydarian et al, 2015cHeydarian et al, 2017). For example, Heydarian et al (2015a) used immersive virtual environments to collect data on behaviours and preferences of occupants in relation to lighting conditions and so evaluating design options aiming to both meet their lighting preferences and, at the same time, increase the energy efficiency of the building.…”
Section: Immersive Virtual Reality In Usability-focused Design Reviewsmentioning
confidence: 99%
“…For example, results of the experimental part of the study conducted by Dunston et al [35] revealed that IVR led to the detection of shortcomings in hospital room layout concerning relationships between spatial properties, such as insufficient clearances between furniture elements or overdimensioned elements. Within the same domain, Bassanino et al [39] conducted design review case study concerned with a redesign of the bathroom for disabled people during which IVR allowed a wheelchair user to test the accessibility of the bathroom presented by the virtual mock-up.…”
Section: ) Studies Of Perception Of Body-scaled Affordancesmentioning
confidence: 99%
“…For that reason, Computer Supported Collaborative Work (CSCW) has been intensively investigated during the last decades [42]. Several tools and frameworks for developing virtual environments, such as VRJuggler [7], COVEN [38], AfreeCA [32] and Cospaces [3], have been developed to explore virtual meeting environments based on distributed Virtual Reality (VR) technology. Whilst these platforms have successfully demonstrated the potential of constructing distributed platforms for creating virtual meetings for remote teams [10], they have not given much attention to the industry context, requirements for multi-disciplinary team interaction, task analysis and the richness of the data required for conducting appropriate team activities, especially within the context of space exploration.…”
Section: Related Workmentioning
confidence: 99%